2018
DOI: 10.1016/j.celrep.2018.08.081
|View full text |Cite
|
Sign up to set email alerts
|

Co-dependent Assembly of Drosophila piRNA Precursor Complexes and piRNA Cluster Heterochromatin

Abstract: In Drosophila, the piRNAs that guide germline transposon silencing are produced from heterochromatic clusters marked by the HP1 homolog Rhino. We show that Rhino promotes cluster transcript association with UAP56 and the THO complex, forming RNA-protein assemblies that are unique to piRNA precursors. UAP56 and THO are ubiquitous RNAprocessing factors, and null alleles of uap56 and the THO subunit gene tho2 are lethal. However, uap56sz15 and mutations in the THO subunit genes thoc5 and thoc7 are viable but ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 55 publications
6
35
0
Order By: Relevance
“…It is plausible that Nxt1 is required for export by Nxf3, or it might function in co-transcriptional recruitment to cargo RNAs. In this regard, it is striking that Nxt1, and also UAP56 and THO complex components are concentrated at piRNA clusters (Zhang et al 2012;Zhang et al 2018), even though these proteins are reportedly essential for general mRNA export.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that Nxt1 is required for export by Nxf3, or it might function in co-transcriptional recruitment to cargo RNAs. In this regard, it is striking that Nxt1, and also UAP56 and THO complex components are concentrated at piRNA clusters (Zhang et al 2012;Zhang et al 2018), even though these proteins are reportedly essential for general mRNA export.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this Rhi-anchored complex generates transcripts that lack signatures of canonical mRNAs. UAP56, a DEAD-box helicase also involved in canonical mRNA splicing and export, was shown to associate with piRNA precursor transcripts (Zhang et al 2012;Zhang et al 2018). Co-localization of UAP56 with the sites of dual-strand cluster transcription and a close association with the perinuclear DEAD-box helicase Vasa (Vas) suggested that this protein is involved in coupling precursor synthesis to downstream processing (Zhang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Export of mRNA from the nucleus requires the association of the heterodimeric nuclear RNA export receptor Nxf1-Nxt1 (Tap-p15) with mRNA cargo, which is enabled by the nuclear RNA helicase UAP56/Hel25E and the associated THO complex, present from yeast to human (Heath et al, 2016;Kohler and Hurt, 2007;Luo et al, 2001;Strasser and Hurt, 2001). In the Drosophila germline, both, UAP56 and the THO complex are enriched at Rhino-dependent piRNA clusters and are required for efficient piRNA production from these loci (Hur et al, 2016;Zhang et al, 2012;Zhang et al, 2018). To ask whether Nxf1-Nxt1 might also export germline piRNA precursors, we generated flies expressing Nxf1 or Nxt1 with a 'localization and affinitypurification' (LAP) tag consisting of GFP and a triple FLAG peptide.…”
Section: Nxf3 Localizes To Pirna Transcription and Processing Sitesmentioning
confidence: 99%
“…Formation of these "mini-clusters", through an uncharacterized epigenetic mechanism, provides an independent adaptation mechanism. In Drosophila, germline piRNA clusters and transposon mini-clusters are bound by the RDC complex, which is composed of the HP1 homolog Rhino (Rhi), which co-localizes with the linker protein Deadlock (Del) and the Rai1 homolog Cutoff (Cuff) (Chang et al, 2019;Chen et al, 2016; Le Thomas et al, 2014;Mohn et al, 2014;Pane et al, 2011;Parhad et al, 2017;Yu et al, 2015;Zhang et al, 2018;Zhang et al, 2014). The three components of the RDC are co-dependent for localization to clusters, and essential to germline piRNA production.…”
Section: Introductionmentioning
confidence: 99%